Slaveries of the first millennium - Rotman, Youval (Past imperfect (ARC Humanities Press), 2021)
In a world where princesses found themselves enslaved, kidnapped boys became army generals, and biblical Joseph was a role model, this book narrates the formation of the Middle Ages from the point of view of slavery, and outlines a new approach to enhance our understanding of modern forms of enslavement. Offering an analysis of recent scholarship and an array of sources, never before studied together, from distinct societies and cultures of the first millennium, it challenges the traditional dichotomy between ancient and medieval slaveries. Revealing the dynamic, versatile, and adaptable character of slavery it presents an innovative definition of slavery as a historical process.